Strengthening the Research Capacities of International Relations Laboratory Assistants in NVivo-Based Qualitative Social Research (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The skill gap in the use of qualitative analysis software remains a challenge for students, especially in social research that requires systematic data management. This study aims to evaluate the effectiveness of NVivo training activities for International Relations laboratory assistants in improving their conceptual understanding and technical skills. The training was conducted through a combination of lectures, demonstrations, and hands-on practice using a know-to-apply model that emphasized immediate application to participants' research needs. The findings show that this training was able to improve participants' understanding of the functions, features, and benefits of NVivo in supporting students' research agendas. In addition, participants assessed that the use of NVivo expanded their analytical capacity and opened up opportunities for optimizing qualitative research in an academic environment. Participants also expressed their hope for the program's continuity and the strengthening of this application's utilization in future research activities. These results emphasize the importance of structured training interventions to bridge the digital skills gap among students and improve the quality of social research.